LITERATURE REVIEW: THE EFFECTIVENESS OF TELEHEALTH-BASED HEALTH EDUCATION ON MOTHERS’ ABILITY TO CARE FOR LOW BIRTH WEIGHT INFANTS - Krissanti, Hanny; Peristiowati, Yuly; Ellina , Agusta Dian; Fajriah, Asruria Sani (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2024)
Background: Knowledge and skills of mothers and families in the care of low birthweight babies are very important to prevent mortality and morbidity, because LBW babies are at risk of experiencing health problems. Care is therefore required from when the baby is hospitalized until the baby is discharged. Purpose: To determine the effectiveness of using telehealth-based health education to increase the knowledge and skills of mothers in caring for LBW infants. Methods: This literature review was conducted based on the search for data sources and selection of articles with references used, namely Google Scholar and PubMed. The keywords used are telehealth OR miHealth OR app health AND low birth weight AND knowledge AND skills. The inclusion criteria for articles taken were those published in full text, in the period 2012-2021, quantitative research types, as well as articles with the main content being the use of health education media regarding the care of LBW babies. The search results contained 38 articles that had been adjusted to the inclusion criteria, there were 6 remaining articles. Results: knowledge and skills of mothers in caring for babies can increase after being given telehealth-based health education compared to conventional health education, namely leaflets and demonstrations. Conclusion: Health education based on telehealth is effective in increasing knowledge and skills so that mothers can care for LBW babies.